JOURNAL OF GOVERNMENT & POLITICS : Ethical Behavior, Work Values and Performance of the Provincial Government Officers of Agusan, delSur, Philippines, in the light of ASEAN Integration - Jed P. Acero (FISIPOL UMY, 2016)
This descriptive-correlation determined the level of ethical behavior, work values and performance of the Provincial Government Officers of Agusan del Sur, Philippines.